Influência de cultivares, do ambiente e de fungicidas na expansão de lesão da mancha-amarela do trigo - Ranzi, Camila (2012)
Wheat is a very important grain crop for Brazil and for the state of Rio Grande do Sul. With the introduction of the nontillage system, tan spot caused by the fungus Pyrenophora triticirepentis (Died.) Drechs, anamorphic phase Drechslera tritici-repentis (Died.) Shoemaker, has increased in importance and caused more losses to the wheat crop. Diseases caused by necrotrophic fungi usually use lesion expansion as a major component to increase their epidemics. Several experiments were performed at UPF in 2010 and 2011 to study the importance of lesion expansion on tan spot epidemics. Initially ten wheat cultivars (BRS Guamirim, Campeiro, Fundacep Horizonte, Fundacep Raízes, Fundacep 52, Marfim, Mirante, Pampeano, Quartzo and Vaqueano) were compared regarding lesion expansion, which differed among cultivars, with the highest values in Fundacep Horizonte and the lowest in Campeiro, Pampeano and Marfim. A second experiment aimed at studying the effect of two ambient temperatures (18 and 25 oC) and two values of relative humidity (70 and 93%) on lesion expansion of cultivars Fundacep Horizonte, Fundacep Raízes and Mirante. The tested temperatures had no effect on lesion size, but it was higher at 93% relative humidity. At the same ambient conditions the fungus did no sporulate within 10 days after inoculation. Lesion expansion was also evaluated regarding its contribution to total disease severity after one, two, or three sequential inoculations on cultivars Fundacep Horizonte, Fundacep Raízes, Mirante, Pampeano and Quartzo. Lesion expansion accounted for more than 80% of the total disease, especially in early stages of the epidemic. The last trials assessed the curative performance of fungicides (one triazol, one strobylurin, and their mix) on lesion expansion. The strobylurin did not differ from the non-treated control. The triazol limited lesion expansion when sprayed few days after inoculation, but it did not differ from the strobylurin if sprayed 10 days after inoculation. Among the commercial fungicides tested propiconazol, trifloxystrobin + protioconazol and fluxapiroxad + epoxiconazol + piraclostrobina constantly provided lower rates of lesion expansion. In conclusion, lesion expansion by tan spot vary significantly among wheat cultivars and can be used as a parameter to evaluate new genotypes for disease susceptibility or resistance. Lesion size is only partially influenced by ambient conditions, it is a major epidemic component and it is difficult to control by curative sprays of fungicide. Therefore the management of tan spot shall include preventive disease control methods, such as crop rotation, seed treatment and earlier sprays of fungicides.